دراسة الوثوقية و تحقيقها باستخدام التواقيع الرقمية - بسام علي مصطفى; ياسين حكمت اسماعيل (PROSPECTIVE RESEARCHES, 2023)
This paper deals with studying Authentication conception and the methods which are used to achieve it focusing on Digital Signature method for the high level of Authentication it provides and the secure way of moving data through computer's net. Also, it is considered one of the new methods in the field. The research proposes a method for Digital Signature depending on the right features and ideas of achieving Authentication methods previously used. The mechanism method includes using the idea of a one way hash function to obtain the Message Digest, and also including Authentication inquiry depending on Symmetric Encryption System which includes providing specific structure to the message which has been designed before. Encryption process includes the procedure of replacing message letters and symbols depending on the statistical features of English. This method provides high level of randomness to the yield text, hence it achieves high degree of Authentication and will secure the moving data through computer's net. It also opens the way before the workers in banking and the commercial sector through using the electronic Net's to cope with the development in this field .